Developing E-Module Integrated of Islamic Values in Mathematics Learning: A Study Three-Dimensional Material - Sitti Marlina Salam; Baharullah Baharullah; Mukhlis Mukhlis (Jurnal Inovasi Pendidikan dan Sains, 2025)
Various certified journals have conducted and disseminated numerous studies on the application of e-modules in mathematics education. Currently, there is no scientific work that examines the application of E-Modules integrated with Islamic values ​​in three-dimensional materials, considering mathematical abilities and the learning approach or model used. This study aims to evaluate the validity, practicality, and effectiveness of e-modules designed based on Islamic values ​​in three-dimensional materials to improve character among high school students in mathematics learning. This research employs a 4-D development model, utilizing data gathered from observations, assessments (pretest and posttest), validation forms, student feedback questionnaires, and observation sheets. The study's results indicated that the e-module was very valid, getting a score of 87.5% from experts; practical, according to observers (3.4) and student feedback (85.71%); and somewhat effective, with a score of 91.4% for effectiveness. The findings suggest that e-modules grounded in Islamic values inside three-dimensional materials effectively enhance learning outcomes and student character in mathematics education.